The Role of Organizational Communication in Increasing Work Morale of Kitchen Employees at the Aryaduta Hotel Manado - Waworuntu, Alfredo Luis; Lagarens, Yollanda Lydia; Kaligis, Stevie (Journal of Multi-Disciplines Science, 2024)
This research aims to analyze the role of organizational communication in kitchen employees' work spirit at the Aryaduta Hotel Manado. This research uses a qualitative method with a case study approach. Data was collected through interviews and field observations with kitchen employees. The research results show that organizational communication is essential in increasing kitchen employee morale: increasing employee motivation, collaboration and job satisfaction. Good organizational communication leads employees to understand the organization's goals, the tasks they carry out, and the expectations given to them. Clear and timely messages also ensure employees have the information they need to do a good job. On the other hand, delays in delivering information have implications for uncertainty and confusion among employees. Lack of team communication can also hinder effective collaboration and coordination in the Kitchen. The implications of this research are essential for hotel management to carry out effective organizational communication in increasing kitchen employee morale. The research results form the basis for further research in the field of organizational communication and employee morale in the hotel industry.